EFFECTS OF STAR APPLE (Chrysophyllum cainito) FRUIT AND PEEL EXTRACT USING BRINE SHRIMP (Artemia salina) LETHALITY ASSAY - Delay, John Michael; Villaraiz, Irish Kaitlyn; Anisco, April A; Frio, Elena F (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The main objectives of the study were to determine the cytotoxic activity of star apple (Chrysophyllum cainito) fruit extract and peel extract using brine shrimp (Artemia salina) effects assay. This study is limited to determine the anticancer potential of the different concentration of star apple (Chrysophyllum cainito) fruit extract and peel extract against the mortality rate of brine shrimp (Artemia salina). Using brine shrimp brine shrimp, the lethal concentration (LC) of a plant extract that results in 50% mortality (LC ₅₀) is measured. Three treatments were prepared (Treatment A – 10 mL star apple (Chrysophyllum cainito) fruit extract, Treatment B – 10 mL star apple (Chrysophyllum cainito) peel extract, Treatment C (Control) – 10 mL Distilled water) with three replicates. Ten brine shrimps were tested for their mortality rate and were recorded after 15, 30, 45, and 60 minutes of application. The different concentration of star apple (Chrysophyllum cainito) fruit extract and peel extract does not have anticancer potential based on the mortality of brine shrimp (Artemia salina) brine shrimp.